A Shear-Thinning, Self-Healing, Dual-Cross Linked Hydrogel Based on Gelatin/Vanillin/Fe3+/AGP-AgNPs: Synthesis, Antibacterial, and Wound-Healing Assessment - Talodthaisong, Chanon; Patramanon, Rina; Thammawithan, Saengrawee; Lapmanee, Sarawut; Maikaeo, Lamai; Sricharoen, Phitchan; Khongkow, Mattaka; Namdee, Katawut; Jantimaporn, Angkana; Kayunkid, Navaphun; Hutchison, James A.; Kulchat, Sirinan (My University, 2023)
A shear-thinning and self-healing hydrogel based on a gelatin biopolymer is synthesized using vanillin and Fe3+ as dual crosslinking agents. Rheological studies indicate the formation of a strong gel found to be injectable and exhibit rapid self-healing (within 10 min). The hydrogels also exhibited a high degree of swelling, suggesting potential as wound dressings since the absorption of large amounts of wound exudate, and optimum moisture levels, lead to accelerated wound healing. Andrographolide, an anti-inflammatory natural product is used to fabricate silver nanoparticles, which are characterized and composited with the fabricated hydrogels to imbue them with anti-microbial activity. The nanoparticle/hydrogel composites exhibit activity against Escherichia coli, Staphylococcus aureus, and Burkholderia pseudomallei, the pathogen that causes melioidosis, a serious but neglected disease affecting southeast Asia and northern Australia. Finally, the nanoparticle/hydrogel composites are shown to enhance wound closure in animal models compared to the hydrogel alone, confirming that these hydrogel composites hold great potential in the biomedical field.
Keywords: andrographolide; antibacterial; gelatin; self-healing hydrogel; silver nanoparticles; vanillin